The Effect of Squat Jump and Box Drill Exercises on Increasing Leg Power in Male Taekwondo Athlete ATIA Lanal Lampung - Ulfa, Anne (Journal of Social Work and Science Education, 2023)
Leg power strength is a very important component aspect in taekwondo martial arts, especially in basic kicking techniques in supporting the optimal kick. There are many modifications to the training model that can increase the power of the kick, one of which is the form of squad jump and box drill training. The purpose of this study was to determine the effect of the two training methods on increasing leg power in Atia Lanal Lampung athletes. The method in this study uses quantitative experimental research methods. In this study, there are 38 populations that will be divided using ordinal pairing with predetermined inclusion criteria, resulting in a total sample of 20 athletes.